Iranian cinema and philosophy : shooting truth - Erfani, Farhang, 1975- (New York, NY : Palgrave MacMillan, 2012)
'In film studies, Iranian films are kept at a distance, as'other,' different, and exotic. In reponse, this book takes these films as philosophically relevant and innovative. Each chapter of this book is devoted to analyzing a single film, and each chapter focuses on one philosopher and one particular aesthetic question'--
Includes bibliographical references (p. [205]-221) and index.
Keywords: Motion pictures -- Iran; Motion pictures -- Philosophy